2015
DOI: 10.1007/s12640-015-9563-7
|View full text |Cite
|
Sign up to set email alerts
|

Hair Cell Loss Induced by Sphingosine and a Sphingosine Kinase Inhibitor in the Rat Cochlea

Abstract: Sphingolipid metabolites including ceramide, sphingosine (Sph), and sphingosine-1-phosphate (S1P) play important roles in the regulation of cell survival and death. Sphingosine kinase (Sk) phosphorylates Sph to S1P. Sk is reportedly overexpressed in various cancer cells, and Sk inhibitors are therefore a target of anti-tumor therapy. However, the effects of Sph and Sk inhibitors on cochlear hair cells were unknown. In the present study, expression of Sk isotypes in the cochlea was examined. In addition, the ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 79 publications
(113 reference statements)
0
6
0
Order By: Relevance
“…The authors demonstrated that administration of an antagonist for S1P 2 , but not S1P 1 and S1P 3 , results in increased gentamycin ototoxicity 43 . They further show that inhibition of sphingosine kinase potentiates cisplatin ototoxicity and itself promotes apoptosis and hair cell loss 44 , which confirms the importance of endogenous S1P signalling in cochlear integrity. Additionally, S1P signalling has been implicated in other cellular and physiological functions in the inner ear 45 .…”
Section: Discussionmentioning
confidence: 64%
“…The authors demonstrated that administration of an antagonist for S1P 2 , but not S1P 1 and S1P 3 , results in increased gentamycin ototoxicity 43 . They further show that inhibition of sphingosine kinase potentiates cisplatin ototoxicity and itself promotes apoptosis and hair cell loss 44 , which confirms the importance of endogenous S1P signalling in cochlear integrity. Additionally, S1P signalling has been implicated in other cellular and physiological functions in the inner ear 45 .…”
Section: Discussionmentioning
confidence: 64%
“…With aging, there could be a lower rate of recruitment of sphingolipid metabolic enzymes such as sphingosine kinase, leading to higher cellular levels of ceramide and sphingosine and lower levels of S1P, ultimately leading to decreased neuronal function. Indeed, inhibition of sphingosine kinase and sphingosine itself mediate hair cell loss in cochlear cells of rats, whereas S1P decreased hair cell loss (Romero-Guevara et al, 2015 ; Tani et al, 2016 ). Furthermore, regulation of S1P levels may impact neurodegenerative disorders.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, other potential pharmacological applications have been recently explored, namely those related with Alzheimer's disease. Low concentrations of SNP (0.01 and 0.1 μM) effectively decreased β‐amyloid production through inhibition of amyloidogenic processing of amyloid precursor protein, while higher concentrations (10 and 20 μM) yielded the opposite outcome …”
Section: Nitric Oxide and Nitroxyl Donorsmentioning
confidence: 97%
“…Low concentrations of SNP (0.01 and 0.1 M) effectively decreased -amyloid production through inhibition of amyloidogenic processing of amyloid precursor protein, while higher concentrations (10 and 20 M) yielded the opposite outcome. 32 Organic nitrates have a rapid onset in lowering blood and cardiac filling pressures, thus being frequently used to treat acute cardiovascular events. 33 GTN (Fig.…”
Section: Nitric Oxide Donorsmentioning
confidence: 99%